Thesaurus on abaca its construction with the application of the UNESCO guidelines for the establishment and development of monolingual thesauri - Rillo, Alicia H.; Tabora, Panfilo (Quezon City Institute of Library Science, University of the Philippines Diliman, 1979)
This paper presents an exercise on the mechanism in the construction of a thesaurus using the UNESCO Guidelines for the Establishment and Development of Monolingual Thesauri as guide. The Guidelines are designed in such a way that they are applicable in all information and documentation centers developing thesauri for information storage and retrieval irrespective of subject field.
Specifically the exercise is applied to agricultural documentation. The particular subject area ia abaca which includes its production and the utilization of its by-products. The Abaca Documentation Center at the Library of the University of the Philippines at Los Baños would need such a thesaurus.
The first part of the paper is the description of the thesaurus structure and the process of the thesaurus construction. The second part is the product of the exercise which is a thesaurus on abaca. It has a categorized listing and an alphabetized listing.
Appendices: leaves 90-132
Mimeographed.
Special Problem (Master of Library Science)
Keywords: Subject headings -- Abaca; Thesauri